Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.3 - Simplifying Radical Expressions - Exercise Set - Page 434: 122


$x^{9}\sqrt[5] (x^{4})$

Work Step by Step

$\sqrt[5] (x^{49})=\sqrt[5] (x^{45}\times x^{4})=\sqrt[5] (x^{45})\times \sqrt[5] (x^{4})=x^{9}\sqrt[5] (x^{4})$ We know that $\sqrt[5] (x^{45})=x^{9}$, because $(x^{9})^{5}=x^{9\times5}=x^{45}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.